(untitled) (Annals of Medical Research, 2021)
Aim: Pneumothorax is one of the important etiologic factors in newborns that causes respiratory distress. Pneumothorax usually occurs in newborns under mechanical ventilation. Respiratory distress syndrome, meconium aspiration syndrome and resuscitation after birth may also cause pneumothorax. In this study, we retrospectively analyzed newborn who were hospitalized for pneumothorax in our newborn intensive care unit.